Antiviral therapeutics directed against RNA dependent RNA polymerases from positive-sense viruses. (October 2021) - Bhatia, Sonam; Narayanan, Naveen; Nagpal, Shilpi; Nair, Deepak T.
Abstract: Viruses with positive-sense single stranded RNA (+ssRNA) genomes are responsible for different diseases and represent a global health problem. In addition to developing new vaccines that protect against severe illness on infection, it is imperative to identify new antiviral molecules to treat infected patients. The genome of these RNA viruses generally codes for an enzyme with RNA dependent RNA polymerase (RdRP) activity. This molecule is centrally involved in the duplication of the RNA genome. Inhibition of this enzyme by small molecules will prevent duplication of the RNA genome and thus reduce the viral titer. An overview of the different therapeutic strategies used to inhibit RdRPs from +ssRNA viruses is provided, along with an analysis of these enzymes to highlight new binding sites for inhibitors.